Design and Implementation of a Web-Based Extracurricular Management System at SMP Negeri 04 Kotabumi - Agustina, Reni; Gunanto, Sigit (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2026)
This study aims to design and implement a web-based extracurricular management information system at SMP Negeri 04 Kotabumi as a solution to issues in managing activities that are still conducted manually. The previous manual process often resulted in registration delays, data recording errors, and difficulties in activity reporting. The system was developed using the Waterfall method, which includes five main stages: requirements analysis, design, coding, testing, and maintenance. During the analysis stage, observations and interviews were conducted on eight active extracurricular activities, involving 15 supervisors and 120 students. The system was designed using PHP, MySQL, and Bootstrap to create a dynamic and easily accessible interface. Testing was conducted by 10 admins/supervisors and 20 students using Black Box Testing, with five trials for each main feature. The results showed a 100% success rate with no functional errors. Moreover, the implementation of this web-based system increased the average time efficiency by 74.5% compared to the previous manual process and enhanced transparency and effectiveness in managing extracurricular activities at the school.